Characterization of peat microbial functional diversity in aerobic rice rhizosphere - Ali Hassan, Nor Ayshah Alia; Mohd Saud, Halimi (Universiti Putra Malaysia Press, 2020)
Microorganisms in the rhizosphere possess numerous metabolic activities. The addition of inorganic substance such as fertilizer could affect the microbial functional diversity. This study was conducted to evaluate the effect of different rate of NPK fertilizer on microbial functional diversity in the rhizosphere of local aerobic rice variety. Aerobic rice variety MRIA 1 was used in this study. Peat was taken from a non-agricultural area in Klang, Malaysia. The effect of fertilizer rate was determined with 4 different rates (C = nonfertilized; T1 = 100 kg/ha NPK; T2 = 200 kg/ha NPK; T3 = 400 kg/ha NPK). Microbial functional diversity was performed using Biolog™ Ecoplate System and measured by microbial activities, such as average well color development (AWCD), species richness (R), Shannon-Weaver index (H index) and species evenness (E). As a result, microbial activity increased to 5.7% when fertilizer applied at T2, while fertilizer rate at T3 increased species richness by 3.2%. However, addition of fertilizer did not affect the H index while species evenness slightly decreased by 1.1% when applied at T3. Bacteria population was reduced when fertilizer added at T1. Fertilizer addition to the peat soil decreased the culturable population of nitrogenfixing microbes while no effect was found on culturable fungal, actinomycetes and phosphate-solubilizing microbe population. Microbes in T2 utilized many carbon sources. Variation in carbon sources used by microbes was found when fertilizer was applied at different rates. D-cellobiose, pyruvic acid methyl ester, and L-serine were the carbon sources that influenced the microbial function in soil. It is concluded that fertilizer has an effect on microbial functional diversity in the peat rhizosphere of local aerobic variety. The recommended fertilizer rate (T2) increased the microbial activity while high fertilizer rate (T3) increased species richness and decreased species evenness.